Synchronization Of Land Administration And Ppat Deeds: A Legal Review Of Efforts To Reduce Overlapping Land Ownership - Ayu Megawati; Maret Priyanta; Yani Pujiwati (UNIVERSITAS PAKUAN, 2026)
Overlapping land ownership is one of the pressing issues in national land governance, leading to an increase in civil and criminal disputes, as well as the criminalization of land administration officials. One of the root problems lies in the lack of synchronization between land administration managed by the Ministry of ATR/BPN and legal documents prepared by PPAT, particularly authentic deeds related to the sale and transfer of land rights. This article aims to examine the strategic role of PP AT in preventing overlapping land ownership through the integration of systems and functions of land administration. The main focus of the study is directed towards the evaluation of the Strategic Plan (RENSTRA) of the Directorate General of Survey and Land Mapping (SPPR) 2020–2024, which emphasizes the acceleration of land registration, as well as analyzing the direction of formulating the RENSTRA 2025–2029, which begins to include the improvement of data quality as a strategic objective. The approach used is juridical-normative and policy analysis. The study results indicate that the disharmony of regulations and the weak integration of data between notarial documents and land information systems increase the potential for overlap. Therefore, this article recommends strengthening structural collaboration between PP AT and the Land Office, as well as reformulating policies in the RENSTRA Ditjen SPPR 2025–2029 to explicitly accommodate the role of PPAT as part of the preventive legal-based agrarian conflict prevention system. Keywords: Overlapping land ownership, PPAT, Land administration, RENSTRA Ditjen SPPR, Agrarian Integration Introduction